Upaya Musyrifah "Pembimbing" dalam Pembentukan Karakter Tanggung Jawab Siswa di Boarding Putri SMA Al-Abidin Surakarta Tahun 2015/2016 - Nurcahya, Eliya; , Dr. Syamsul Hidayat, M.Ag (2016)
Shaping a responsible character of student is not easy thing for educators. In Female Boarding School of SMA Al-Abidin of Surakarta, a musyrifah "guide" has duty of educating and guiding moral and religious activity of students, including shaping responsible character among students. Then, efforts of the musyrifah "guide" are needed to shape students with responsible character in the Female Boarding School of SMA Al-Abidin, Surakarta. Purpose of the research is to know and describe effort, method and obstacle factors facing musyrifah "guide" in shaping responsible character of students of the Female Boarding School of SMA Al-Abidin of 2015/2016 in Surakarta. The research is a field one. It used qualitative method. Data was collected by using interview, observation and documentation t methods. Data of the research was analyzed by using descriptive-qualitative analysis. Conclusion was drawn by using deductive-inductive method based on the data analysis. Based on the data analysis, it can be concluded that efforts of musyrifah "guide" in shaping responsible character among students consisting of: a) performing a take and give; b) making muttaba'ah yaumi and checked it every day; c) implementing agenda and rules according to what has been arranged in the boarding; d) providing advices in general and in personal, and continuously providing reminders to students; e) making a checklist of laptop circulation and learning which had been socialized in mentoring and then, inspect and observe it; f) keeping record of violations, permission note of using a laptop, as data and document of students; g) checking students who have duty of cleaning classroom; h) observing document and daily activities of students and then provide rewards; i) involving students' organization to determine sanction so that a violation will be sanctioned as agreed jointly as a form of consequence. Methods of musyrifah "guide" in shaping responsible character of students can include methods of providing good example, habituation, advices, rewards and sanction or penalty, embedding and enforcing discipline, and creating a conducive atmosphere. Researcher discovered other method, namely learning method, patience method, perseverance method, and istiqomah (determination) method in guiding students. Obstacle factors of the responsible character shaping were too tolerant musyrifah "guide", small gap of ages between student and musyrifah "guide" so that students were less respecting musyrifah "guide", students considered trivially the rules of conduct of the boarding, influence of other students, less understanding about responsibility, less mature of thinking, childish thinking, and a weak intent in attending the boarding.